Evaluation of a neem (Azadirachta indica) herbal formulation for management of sarcoptic mange in dromedary camels - Tej Prakash Atal; Narnaware, Shirish Dadarao; Choudhary, Sunita; Sawal, Rajesh Kumar; Ranjan, Rakesh (Indian Journal of Veterinary Medicine, 2024)
In the present study, a neem herbal formulation was prepared using fresh neem leaves, mustard oil, turmeric powder, camphor oil and distilled water for treatment of sarcoptic mange in adult dromedary camels. Total seven applications of this formulation was applied in six mange affected camels at every alternate day. The efficacy of this formulation was compared with six camels receiving two doses of ivermectin injection (dose rate 0.2mg/Kg body weight) at 7 days interval. To evaluate the therapeutic efficacy of the formulation, improvement in skin lesions of mange were recorded, and skin scraping and skin biopsy examination was performed before and after treatment. Macroscopically all the mange affected camels showed grey colored dry skin lesions over different body parts with intense pruritus, alopecia, thickening and corrugation. At the end of treatment trial, the neem formulation treated camels showed complete recovery without any remnants of scar or keratinization at affected sites, further the skin became smooth, shiny and glossy with appearance of new hair growth. In ivermectin treated camels although recovery from mange lesions was observed after14th day, however the grey areas of the skin with some remnants of scar or keratinization and patches of alopecia were not completely cured in 50% of the treated camels. The result indicated that neem based herbal formulation have better efficacy than ivermectin against treatment of sarcoptic mange in dromedary camels and can provide a cheap, safe and eco-friendly alternative.